3D Printing‐Enabled Nanoparticle Alignment: A Review of Mechanisms and Applications. Issue 45 (27th June 2021) - Xu, Weiheng; Jambhulkar, Sayli; Ravichandran, Dharneedar; Zhu, Yuxiang; Kakarla, Mounika; Nian, Qiong; Azeredo, Bruno; Chen, Xiangfan; Jin, Kailong; Vernon, Brent; Lott, David G.; Cornella, Jeffrey L.; et al.
Abstract: 3D printing (additive manufacturing (AM)) has enormous potential for rapid tooling and mass production due to its design flexibility and significant reduction of the timeline from design to manufacturing. The current state‐of‐the‐art in 3D printing focuses on material manufacturability and engineering applications. However, there still exists the bottleneck of low printing resolution and processing rates, especially when nanomaterials need tailorable orders at different scales. An interesting phenomenon is the preferential alignment of nanoparticles that enhance material properties. Therefore, this review emphasizes the landscape of nanoparticle alignment in the context of 3D printing. Herein, a brief overview of 3D printing is provided, followed by a comprehensive summary of the 3D printing‐enabled nanoparticle alignment in well‐established and in‐house customized 3D printing mechanisms that can lead to selective deposition and preferential orientation of nanoparticles. Subsequently, it is listed that typical applications that utilized the properties of ordered nanoparticles (e.g., structural composites, heat conductors, chemo‐resistive sensors, engineered surfaces, tissue scaffolds, and actuators based on structural and functional property improvement). This review's emphasis is on the particle alignment methodology and the performance of composites incorporating aligned nanoparticles. In the end, significant limitations of current 3D printing techniques are identified together with future perspectives. Abstract : A brief overview of 3D printing, followed by a comprehensive summary of the 3D printing‐enabled nanoparticle alignment and their effects on material properties for a broad range of applications is presented. In the end, significant limitations of current 3D printing techniques are identified, and future perspectives for next‐generation manufacturing with multiscale, multimaterial, and multifunctional capabilities are provided.